Current smoking is associated with lower seminal vesicles and ejaculate volume, despite higher testosterone levels, in male subjects of infertile couples - Lotti, F.; Corona, G.; Vitale, P.; Maseroli, E.; Rossi, M.; Fino, M.G.; Maggi, M. (Human reproduction (Oxford), 2015)
STUDY QUESTION What is the impact of smoking behaviour on seminal, hormonal and male genital tract ultrasound parameters in subjects seeking medical care for couple infertility? STUDY ANSWER In males of infertile couples, current smokers (CS), when compared with non-smokers, show lower ejaculate and ultrasound-derived seminal vesicles (SV) volume, despite higher testosterone levels. WHAT IS KNOWN ALREADY Data on the effects of smoking on male fertility are conflicting. A correlation between smoking and reduced semen parameters has been reported, however, with a high heterogeneity among studies. An association between smoking behaviour and higher testosterone levels in men has been described in several, but not all, the previous studies. No study has systematically evaluated the impact of smoking on the male genital tract ultrasound characteristics. STUDY DESIGN, SIZE AND DURATION Retrospective cross-sectional analysis of a consecutive series of 426 subjects seeking medical care for couple infertility from January 2010 to July 2013. PARTICIPANTS/MATERIALS, SETTING, METHODS From the entire cohort, 394 men (age 36.0 ± 8.0 years) free of genetic abnormalities were selected. All subjects underwent a complete andrological and physical examination, biochemical and hormonal assessment, scrotal and transrectal colour-Doppler ultrasound and semen analysis (including seminal interleukin-8 levels, sIL-8) within the same day. MAIN RESULTS AND THE ROLE OF CHANCE Among the patients evaluated, 229 were never smokers (NS), 56 past smokers (PS) and 109 CS. When CS were compared with the rest of the sample (non-smokers, NS + PS), in a multivariate model (analysis of covariance, ANCOVA) adjusted for age, lifestyle (including alcohol, cannabis and physical activity), BMI and sex hormone-binding globulin, significantly higher androgen (total testosterone, P = 0.001; calculated free testosterone, P < 0.005) and lower FSH (P < 0.05) levels were observed in CS. However, when total testosterone was also included in the multivariate model as a further covariate, the difference in FSH levels was not confirmed. In a similar model, a lower ejaculate volume (P < 0.01) and a higher prevalence of normal sperm morphology (P < 0.02) were also detected in CS in comparison with the rest of the sample. However, when total testosterone was also included in the multivariate model as a further covariate, only the difference in ejaculate volume between CS and non-smokers was confirmed (−0.61 ± 0.23 ml, P < 0.01). Finally, CS showed lower total SV volume, before and after ejaculation, even after adjusting for confounders (P = 0.02 and <0.01, respectively). Similar results were observed when the reported number of cigarettes smoked or the number of pack-years was considered separately. LIMITATIONS, REASONS FOR CAUTION The present results are derived from patients consulting an Andrology Clinic for couple infertility, who could have different characteristics from the general male population or males consulting general practitioners for reasons other than couple infertility. In addition, we did not have a true control group composed of age-matched, apparently healthy, fertile men, and therefore true normative data of sonographic parameters cannot be inferred. Due to the cross-sectional nature of our study, neither a causality hypothesis nor mechanistic models can be drawn. Finally, this is a retrospective study, and further prospective studies are required. WIDER IMPLICATIONS OF THE FINDINGS We report an apparent paradox in CS: lower SV volume despite higher testosterone levels. Our data suggest that smoking may negatively affect SV volume in an independent manner, as the difference between CS and non-smokers retained significance after adjusting for confounders including testosterone. This is the first study reporting such ultrasound evidence. How this new smoking-related alteration, along with low semen volume, impacts male fertility needs to be addressed by further studies. STUDY FUNDING/COMPETING INTEREST(S) No funding was received for the study. None of the authors have any conflict of interest to declare.